2012
DOI: 10.1126/scitranslmed.3003783
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Microbiome Diversity Depletion and Corynebacterium tuberculostearicum Enrichment Mediates Rhinosinusitis

Abstract: Persistent mucosal inflammation and microbial infection are characteristics of chronic rhinosinusitis (CRS). Mucosal microbiota dysbiosis is found in other chronic inflammatory diseases; however, the relationship between sinus microbiota composition and CRS is unknown. Using comparative microbiome profiling of a cohort of CRS patients and healthy subjects, we demonstrate that the sinus microbiota of CRS patients exhibits significantly reduced bacterial diversity compared with that of healthy controls. In our c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
474
4
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 377 publications
(531 citation statements)
references
References 50 publications
33
474
4
14
Order By: Relevance
“…house environment | airway adaptive immunity | gastrointestinal bacterial community | Lactobacilliaceae T he emerging field of human microbiome research has demonstrated the key role microbial communities play in a variety of critical mammalian processes including ancillary mucosal barrier function (1) and metabolism (2,3), as well as development and modulation of host immune responses (4,5). This is particularly evident in the gastrointestinal (GI) tract where the composition of the microbiome in this niche and, specifically, the presence of particular bacterial species such as segmented filamentous bacteria and those belonging to Clostridium clades IV and XIV, have been shown to induce specific T-cell repertoires, i.e., Th17 and CD4 + FoxP3 + T-regulatory cells, respectively (4,6).…”
mentioning
confidence: 99%
“…house environment | airway adaptive immunity | gastrointestinal bacterial community | Lactobacilliaceae T he emerging field of human microbiome research has demonstrated the key role microbial communities play in a variety of critical mammalian processes including ancillary mucosal barrier function (1) and metabolism (2,3), as well as development and modulation of host immune responses (4,5). This is particularly evident in the gastrointestinal (GI) tract where the composition of the microbiome in this niche and, specifically, the presence of particular bacterial species such as segmented filamentous bacteria and those belonging to Clostridium clades IV and XIV, have been shown to induce specific T-cell repertoires, i.e., Th17 and CD4 + FoxP3 + T-regulatory cells, respectively (4,6).…”
mentioning
confidence: 99%
“…Boase et al 9 and Choi et al 11 found an increased bacterial load in CRS patients and suggested that a rise in bacteria, possibly from external sources, causes CRS. However, Abreu et al, 10 , Feazel et al 12 and Ramakrishnan et al 13 found no difference in burden between the two groups.…”
Section: Bacterial Loadmentioning
confidence: 97%
“…16 , Corynebacterium spp. 10,16 , certain Streptococcus spp., Staphylococcus aureus, Propionibacterium acnes and Haemophilus influenzae 15,16 have been reported in CRS. Abreu et al 10 notably found enrichment of a novel sinopathogen Corynebacterium tuberculostearicum, typically a commensal when present on skin.…”
Section: Balance Of Bacterial Taxamentioning
confidence: 99%
See 2 more Smart Citations